1997
DOI: 10.1073/pnas.94.5.1967
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione deficiency is associated with impaired survival in HIV disease

Abstract: Glutathione (GSH), a cysteine-containing tripeptide, is essential for the viability and function of virtually all cells. In vitro studies showing that low GSH levels both promote HIV expression and impair T cell function suggested a link between GSH depletion and HIV disease progression. Clinical studies presented here directly demonstrate that low GSH levels predict poor survival in otherwise indistinguishable HIV-infected subjects. Specifically, we show that GSH deficiency in CD4 T cells from such subjects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
364
4
10

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 620 publications
(388 citation statements)
references
References 40 publications
10
364
4
10
Order By: Relevance
“…The recent findings of PETERSON et al [231] regarding the importance of GSH levels in antigen-presenting cells in modulating T-helper (Th) cell 1 versus Th2 cytokine response patterns in immune responses to the nature of the antigen, and the decreased intracellular levels of GSH in peripheral blood lymphocytes of CF and HIV-seropositive patients [144,232], led to the assumption that this important tripeptide thiol may be involved in the functional regulation of the immune response. However, the impact of chronic GSH depletion in T-cells, B-cells, macrophages and neutrophils in immune/inflammatory lung diseases have not been studied so far.…”
Section: Immune Effector Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The recent findings of PETERSON et al [231] regarding the importance of GSH levels in antigen-presenting cells in modulating T-helper (Th) cell 1 versus Th2 cytokine response patterns in immune responses to the nature of the antigen, and the decreased intracellular levels of GSH in peripheral blood lymphocytes of CF and HIV-seropositive patients [144,232], led to the assumption that this important tripeptide thiol may be involved in the functional regulation of the immune response. However, the impact of chronic GSH depletion in T-cells, B-cells, macrophages and neutrophils in immune/inflammatory lung diseases have not been studied so far.…”
Section: Immune Effector Responsementioning
confidence: 99%
“…However, the impact of chronic GSH depletion in T-cells, B-cells, macrophages and neutrophils in immune/inflammatory lung diseases have not been studied so far. Chronic depletion of GSH may be coupled with immunodeficiency and poor survival, as evidenced in the CD4 T-cells of HIV-seropositive patients [8,21,232,233]. Intracellular redox GSH levels in these immune/inflammatory cells may also effect signal transduction and activation of transcription factors and lead to elevated gene expression (e.g.…”
Section: Immune Effector Responsementioning
confidence: 99%
“…Clinical use of NAC has shown replenishment of GSH levels in HIV-positive (Herzenberg et al, 1997) and cystic fibrosis patients (Meyer et al, 1995). NAC usage has been suggested for neurodegenerative disorders like Alzheimer's disease or Parkinson's disease (Deigner et al, 2000), but there are no clinical studies supporting its use in MS. Interestingly, oral administration of NAC did inhibit acute EAE in mice (Lehmann et al, 1994) and recent data revealed that NAC amide protects against EAE by scavenging ROS and reducing matrix metalloproteinase-9 (MMP-9) activity .…”
Section: Thiol-based Antioxidantsmentioning
confidence: 99%
“…Herein we addressed the question as to whether glutathione deficiency might be causally linked to the exacerbated TNF-α activation occurring in well-established CHF, as this was observed in several other chronic diseases including HIV infection [13,14], neurodegeneration [1,15], muscular fatigue [14], rheumatoid arthritis [3] and chronic lung diseases [16,17]. Of note, the well-being of the patients affected with those diseases is improved by treatment with the glutathione precursor N-acetylcysteine (NAC) [13,14,18,19]. Previous studies pointed out the decrease in cardiac GSH/ GSSG ratio in CHF [20,21].…”
Section: Introductionmentioning
confidence: 99%